2007
DOI: 10.1016/j.vetimm.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Failure of antigen-stimulated γδ T cells and CD4+ T cells from sensitized cattle to upregulate nitric oxide and mycobactericidal activity of autologous Mycobacterium avium subsp. paratuberculosis-infected macrophages

Abstract: The function of γδ T cells during ruminant paratuberculosis (Johne's disease) is presently unknown. An ex vivo system was used to test the hypothesis that γδ T cells are capable of activating Mycobacterium avium subsp. paratuberculosis-(M. paratuberculosis)-infected macrophages. Peripheral blood-derived macrophages were infected in vitro with live M. paratuberculosis, and autologous LN-derived γδ T cells or CD4+ T cells were co-cultured with infected macrophages for 48 hours, at which time bacterial survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…Evidence from murine studies suggests that gd T cells play an important role in the development of granuloma in mycobacterial infection (D'Souza et al 1997;Saunders et al 1998) Tanaka, 2000 #515} rather than in the intracellular killing of the organism (Simutis et al 2007). The antigen specific proliferation of CD4 + and CD8 + T cells in blood remains enhanced from early to late stages of disease (4-13 months p.i.).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from murine studies suggests that gd T cells play an important role in the development of granuloma in mycobacterial infection (D'Souza et al 1997;Saunders et al 1998) Tanaka, 2000 #515} rather than in the intracellular killing of the organism (Simutis et al 2007). The antigen specific proliferation of CD4 + and CD8 + T cells in blood remains enhanced from early to late stages of disease (4-13 months p.i.).…”
Section: Discussionmentioning
confidence: 99%
“…paratuberculosis-infected bovine macrophages (74), the hyporesponsiveness in ileal lymphocytes from Mycobacterium avium subsp. paratuberculosis-infected cows (75), abnormalities in the regulation of cytokine expression (9,13,16,30,31,65,73), the perturbation of macrophage activation and apoptosis (13,15), and the impairment of nitric oxide responsiveness (61 (33,35,68). Local and systemic immune dysfunctions in humans are well-described features of Crohn's disease (39,46).…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium avium subsp. paratuberculosis infection in cases of Johne's disease is associated with a chronic enteric neuritis (6,29), together with immune activation and dysregulation (15,16,61,65,74,75).…”
mentioning
confidence: 99%
“…The M. avium subsp. paratuberculosis inoculum used in these studies was shown to be above 90% viable as checked via fluorescein diacetate staining and flow cytometry analysis (20,48). Two animals were given an injection of 5 ϫ 10 8 CFU live M. avium subsp.…”
Section: Animalsmentioning
confidence: 99%